Analisis Kemampuan Multirepresentasi Verbal dan Gambar pada Mahasiswa Pendidikan Fisika dalam Memahami Konsep Reaksi Inti Matahari - Okta Nur Aisyah; Sudarti S (SILAMPARI JURNAL PENDIDIKAN ILMU FISIKA, 2021)
Multirepresentative ability is the ability to use several media to assist in teaching or material achievement. Multi-representation ability is usually used by educators to make it easier to convey the material provided to students so that it can be understood more by students. Verbal Multirepresentation Ability is a person's ability to understand a theory using verbal sentence instruments. Meanwhile, the ability of multi-representation images is a person's ability to understand a theory using image media. Physics students learn the concepts of the Solar Core Reaction. The Sun's Core Reaction Theory is one that we cannot see directly in our lives but that we can benefit from. The purpose of this study was to analyze the student's ability to analyze a problem using a verbal approach to understanding this material. This research uses descriptive quantitative method. Of the two shortener between the verbal approach and the pictorial approach from the results of this study, students tended to better understand verbal questions with sentences that they were familiar with during their education or with familiar words among physics students compared to pictures that they were not sure if they were what they were. intended because in some books it does not show illustrations or other supporting images to complement the explanation of a theory.